Positive electrode for lithium secondary battery and lithium secondary battery including the same

The combination of large and small lithium iron phosphate particles with a polytetrafluoroethylene binder in a dry process addresses the energy density limitations of lithium secondary battery electrodes, achieving high energy and current densities through optimized mixing and adhesive strength.

JP2025056704AActive Publication Date: 2025-04-08SAMSUNG SDI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024084942
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-05-24
Publication Date
2025-04-08
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

Existing lithium secondary battery electrodes, particularly those produced via wet processes, face challenges in achieving high energy density due to low loading levels and adhesive strength issues when using lithium iron phosphate particles, leading to uneven coatings and side reactions.

Method used

A positive electrode for lithium secondary batteries is developed using a dry process that combines large and small lithium iron phosphate particles with a polytetrafluoroethylene binder, optimizing the mixing ratio and shear force to form a high-energy density electrode.

Benefits of technology

The dry process enables the production of a positive electrode with improved loading levels and adhesive strength, resulting in a high energy density of 400 Wh/L to 490 Wh/L and a current density of 5 mAh/cm² to 8 mAh/cm², surpassing the limitations of wet process electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056704000001_ABST
    Figure 2025056704000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode for a lithium secondary battery with high energy density.SOLUTION: With regard to positive electrode for a lithium secondary battery and a lithium secondary battery containing the same, a positive electrode includes a dry positive electrode active material layer containing large-grain lithium iron phosphate particles and small-grain lithium iron phosphate particles as positive electrode active materials and a polytetrafluoroethylene binder.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0002] Lithium secondary batteries are batteries that exhibit excellent discharge voltages and high energy densities.

[0003] The electrodes of such lithium secondary batteries can be formed using a wet or dry process, and among these, research is currently being conducted on the dry process, which has a higher capacity and is a simpler process. Summary of the Invention [Problem to be solved by the invention]

[0004] One embodiment is to provide a positive electrode for a lithium secondary battery having a high energy density.

[0005] Another embodiment provides a lithium secondary battery comprising the positive electrode.

[0006] One embodiment provides a positive electrode for a lithium secondary battery comprising a dry positive electrode active material layer including a positive electrode active material of large-grain lithium iron phosphate particles and small-grain lithium iron phosphate particles, and a polytetrafluoroethylene binder.

[0007] Another embodiment provides a lithium secondary battery comprising: the positive electrode; a positive electrode; and a non-aqueous electrolyte.

[0008] Further details of embodiments of the present invention are included in the following detailed description.

[0009] The positive electrode for a lithium secondary battery according to an embodiment may exhibit high energy density. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described in detail, but they are given by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims set forth below. The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.

[0012] As used herein, "combinations thereof" can mean mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0013] As used herein, terms such as "comprise," "include," "comprise," or "have" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, and are not to be understood as precluding the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0014] In the drawings, thicknesses are exaggerated to clearly depict multiple layers and regions, and similar parts are designated by the same reference numerals throughout the specification. When a part, such as a layer, film, region, plate, etc., is said to be "on" or "above" another part, this includes not only when it is "directly on" the other part, but also when there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0015] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0016] As used herein, "or" is not to be construed in its exclusive sense; for example, "A or B" is to be construed as including A, B, A+B, etc.

[0017] Unless otherwise defined in this specification, the particle size or size may be the average particle size. The average particle size refers to the average particle size (D50) which means the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution. The average particle size (D50) can be measured by a method widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with a transmission electron microscope or a scanning electron microscope. As another method, the average particle size (D50) can be obtained by measuring with a measuring device using dynamic light-scattering, analyzing the data, counting the number of particles for each particle size range, and then calculating the average particle size (D50) value.

[0018] A positive electrode for a lithium secondary battery according to one embodiment includes a dry positive electrode active material layer including positive electrode active materials of large lithium iron phosphate particles and small lithium iron phosphate particles, and a polytetrafluoroethylene binder.

[0019] Such a positive electrode refers to a positive electrode that is manufactured without using a solvent, that is, a positive electrode that is manufactured using a dry process instead of a wet process.

[0020] In one embodiment, the positive electrode active material is a lithium iron phosphate particle, and the particle includes two different types of lithium iron phosphate particles, for example, the positive electrode active material may be large lithium iron phosphate particles and small lithium iron phosphate particles. The large lithium iron phosphate particles may be larger in size than the small lithium iron phosphate particles. The size of the lithium iron phosphate particles may be the average particle size, which may be the average particle size (D50). Since the large lithium iron phosphate particles and the small lithium iron phosphate particles are included in the positive electrode active material, a positive electrode suitable for a dry battery can be provided, and thus a positive electrode having a high energy density can be provided. When a positive electrode active material layer is formed using a lithium iron phosphate particle positive electrode active material through a wet process using a solvent, the content of lithium iron phosphate particles capable of being coated is low, and the loading level cannot be improved, and as a result, a high energy density cannot be obtained. Since the positive electrode according to an embodiment is a dry positive electrode, the loading level can be improved, and a positive electrode having a high energy density can be obtained.

[0021] If only large or small lithium iron phosphate particles are used as the positive electrode active material, the adhesive strength to the current collector may decrease when manufacturing a dry positive electrode together with a polytetrafluoroethylene binder, and an uneven coating may be formed when manufacturing a positive electrode with a large area.

[0022] The mixing ratio of the large lithium iron phosphate particles to the small lithium iron phosphate particles may be 99:1 to 60:40 by weight, 95:5 to 65:35 by weight, 80:20 to 60:40 by weight, or 80:20 to 70:30 by weight. When the mixing ratio of the large lithium iron phosphate particles to the small lithium iron phosphate particles is within the above range, the dry cathode active material layer can be more effectively formed, and a cathode having a higher energy density can be obtained.

[0023] In one embodiment, the size of the large lithium iron phosphate particles may be larger than the size of the small lithium iron phosphate particles. For example, the ratio of the size of the large lithium iron phosphate particles to the size of the small lithium iron phosphate particles may be 1.5:1 to 19:1, 1.5:1 to 10:1, or 2:1 to 10:1. When the ratio of the size of the large lithium iron phosphate particles to the size of the small lithium iron phosphate particles is within the above range, a positive electrode having a very high current density, for example, 5 mAh / cm 2 It is possible to manufacture a positive electrode having a current density equal to or higher than this, and thus it is possible to manufacture an ultra-thick film dry positive electrode.

[0024] The size of the large lithium iron phosphate particles may be 2.5 μm to 20 μm, or 2.5 μm to 15 μm, or 5 μm to 15 μm.

[0025] The size of the small lithium iron phosphate particles may be 0.1 μm to 2.5 μm, or 0.1 μm to 2 μm, or 0.5 μm to 2.0 μm.

[0026] When the size ratio of the large lithium iron phosphate particles to the small lithium iron phosphate particles satisfies the above range, and the size of each angle between the large lithium iron phosphate particles and the small lithium iron phosphate particles satisfies the above range, a sufficient shear stress can be transmitted to a binder used in manufacturing a dry positive electrode, making it possible to manufacture a dry positive electrode, and even when a lithium iron phosphate positive electrode active material that generally has a low energy density is used, a positive electrode having high loading and high energy density can be obtained.

[0027] In one embodiment, the large lithium iron phosphate particles and the small lithium iron phosphate particles may be the same or different. The lithium iron phosphate particles are represented by the following chemical formula 1:

[0028] [Chemical formula 1] Li a Fe 1-xM x PO 4 (In the above chemical formula 1, 0.90≦a≦1.8, 0≦x≦0.7, M is Mg, Co, Ni, Mn or a combination thereof.

[0029] In one embodiment of the positive electrode active material layer, the polytetrafluoroethylene binder may be fibrillated polytetrafluoroethylene. Since the polytetrafluoroethylene binder is fibrillated, for example, when a shear force is applied, the binder is mixed with a positive electrode active material, and when a shear force is applied, the fibrillated binder and the positive electrode active material are entangled to form a positive electrode active material layer, so that a dry positive electrode can be manufactured. Such a dry positive electrode is possible when large lithium iron phosphate particles and small lithium iron phosphate particles having different sizes are used together as a positive electrode active material. If only small lithium iron phosphate particles are used as a positive electrode active material, fiberization is not possible and a dry positive electrode cannot be manufactured. In addition, if only large lithium iron phosphate particles are used as a positive electrode active material, sufficient fiberization is difficult, and particle cracks occur during charging and discharging, and side reactions of the electrolyte occur excessively, which is not appropriate.

[0030] In one embodiment, the content of the positive electrode active material may be 95% by weight to 99.9% by weight, 97% by weight to 99.5% by weight, or 97.4% by weight to 99.4% by weight, relative to 100% by weight of the dry positive electrode active material layer.

[0031] The content of the polytetrafluoroethylene binder may be 0.1 wt% to 5 wt%, 0.5 wt% to 3.0 wt%, or 0.6 wt% to 2.6 wt%, based on 100 wt% of the total dry positive electrode active material layer. When the content of the polytetrafluoroethylene binder is within the above range, the dry positive electrode active material layer can be effectively formed.

[0032] The positive electrode active material layer may further include a conductive material. When the positive electrode active material layer further includes a conductive material, the content of the positive electrode active material relative to 100% by weight of the positive electrode active material layer may be 90% by weight to 99% by weight, 94% by weight to 99% by weight, or 96% by weight to 99% by weight, the content of the binder may be 0.5% by weight to 5% by weight, 0.5% by weight to 3% by weight, or 0.5% by weight to 2% by weight, and the content of the conductive material may be 0.5% by weight to 5% by weight, 0.5% by weight to 3% by weight, or 0.5% by weight to 2% by weight.

[0033] The conductive material is used to impart electrical conductivity to the electrodes, and any conductive material can be used as long as it does not undergo chemical changes in the battery that is constructed. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof. The carbon black can include, for example, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, or a combination thereof. The current collector may be made of Al, but is not limited thereto.

[0034] The positive electrode according to one embodiment can exhibit an energy density of 400 Wh / L to 490 Wh / L. In one embodiment, the energy density of the positive electrode can be 400 Wh / L to 450 Wh / L, or 450 Wh / L to 480 Wh / L. Thus, the positive electrode according to one embodiment can exhibit a high energy density.

[0035] The loading level of the dry positive electrode active material layer is 40 mg / cm 2 ~90mg / cm 2 40 mg / cm 2 ~80mg / cm 2The positive electrode active material layer according to an embodiment may thus exhibit a high loading level.

[0036] In addition, the positive electrode has a capacity of 5 mAh / cm 2 The positive electrode has a high current density of 5 mAh / cm or more. 2 ~8mAh / cm 2 It can also be 6mAh / cm 2 ~8mAh / cm 2 It can be.

[0037] <Manufacturing method of positive electrode> A positive electrode according to one embodiment can be prepared as follows.

[0038] A positive electrode active material is manufactured by mixing large lithium iron phosphate particles and small lithium iron phosphate particles. The positive electrode active material is dry-mixed with a polytetrafluoroethylene binder and optionally a conductive material, and the mixture is pressed out to manufacture a positive electrode active material layer. The dry mixing step does not use a solvent. The dry mixing step can be performed at a speed of 1000 rpm to 10000 rpm, 1500 rpm to 8000 rpm, or 2000 rpm to 7000 rpm, and can be performed at this speed for 1 minute to 30 minutes. In this dry mixing step, the polytetrafluoroethylene binder can be fibrillated.

[0039] The positive electrode active material layer may be in the form of a sheet, or a self-standing film.

[0040] The positive electrode is manufactured by attaching the positive electrode material layers to a current collector, which may be, but is not limited to, a lamination process.

[0041] <Lithium secondary battery> A lithium secondary battery according to another embodiment includes the positive electrode, a negative electrode, and a non-aqueous electrolyte.

[0042] <Negative electrode> The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector.

[0043] The negative electrode active material layer contains a negative electrode active material.

[0044] The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping with lithium, or a transition metal oxide.

[0045] Examples of the material capable of reversibly inserting / desorbing lithium ions include carbon-based negative electrode active materials, which can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon can include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon can include soft carbon or hard carbon, mesophase pitch carbide, fired coke, and the like.

[0046] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0047] As the material capable of doping and dedoping with lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), an Si-Q alloy (where Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO 2 , an Sn-based alloy, or a combination thereof.

[0048] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) in which silicon particles are assembled, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the silicon particles, for example, silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0049] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles and an amorphous carbon coating layer located on the core.

[0050] The silicon particles may be silicon nanoparticles.

[0051] The particle size of the silicon nanoparticles may be 10 nm to 1,000 nm, and in another embodiment, 10 nm to 200 nm, or 20 nm to 150 nm. When the particle size of the silicon nanoparticles is within this range, excessive volume expansion during charging and discharging can be suppressed, and conductive path disconnection due to particle crushing during charging and discharging can be prevented.

[0052] In an embodiment of the negative electrode active material, the core silicon-carbon composite may include silicon nanoparticles and an amorphous carbon coating layer disposed on the silicon nanoparticles. The silicon-carbon composite may also include an assembly of at least one silicon nanoparticle and an amorphous carbon coating layer disposed on the assembly.

[0053] In the amorphous carbon coating layer, the amorphous carbon may be soft carbon or hard carbon, mesophase pitch carbide, calcined coke, or a combination thereof. The thickness of the amorphous carbon coating layer may be 1 nm to 2 μm, 1 nm to 500 nm, 10 nm to 300 nm, or 20 nm to 200 nm. When the thickness of the amorphous carbon coating layer is within the above range, the volume expansion of silicon during charging and discharging can be well suppressed.

[0054] The crystalline carbon may be amorphous, plate-like, flake-like, spherical or fibrous natural graphite, artificial graphite, or a combination thereof.

[0055] When the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating layer, the content of the silicon nanoparticles may be 30% to 70% by weight, or 40% to 65% by weight, based on 100% by weight of the entire silicon-carbon composite. Also, the content of the amorphous carbon coating layer may be 30% to 70% by weight, or 35% to 60% by weight, based on 100% by weight of the entire silicon-carbon composite.

[0056] When the silicon-carbon composite further contains crystalline carbon, the content of the silicon nanoparticles may be 20% by weight to 70% by weight or 25% by weight to 65% by weight, based on 100% by weight of the entire silicon-carbon composite. The content of amorphous carbon may be 25% by weight to 70% by weight or 25% by weight to 60% by weight, and the content of crystalline carbon may be 1% by weight to 20% by weight or 5% by weight to 15% by weight, based on 100% by weight of the entire silicon-carbon composite.

[0057] In the negative electrode active material layer, the content of the negative electrode active material may be 95% by weight to 98% by weight with respect to 100% by weight of the entire negative electrode active material layer.

[0058] The negative electrode active material layer may include a binder and may further include a conductive material. The content of the binder may be 1 wt% to 5 wt% with respect to 100 wt% of the total negative electrode active material layer. The content of the conductive material may be 1 wt% to 5 wt% with respect to 100 wt% of the total negative electrode active material layer.

[0059] The binder serves to adhere the negative active material particles to each other and to the current collector well. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0060] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0061] The aqueous binder may be selected from styrene-butadiene rubber, (meth)acrylate styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0062] The binder of the negative electrode may be a cellulose-based compound, and the cellulose-based compound may be used together with the aqueous binder. The cellulose-based compound may be a mixture of one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof. The alkali metal may be Na, K, or Li. The cellulose-based compound may function as a binder or as a thickener that can impart viscosity. The cellulose-based compound may be used at an appropriate content within the binder content, for example, 0.1 to 3 parts by weight per 100 parts by weight of the negative electrode active material.

[0063] The dry binder is a polymeric material that can be fiberized, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0064] The conductive material is used to impart conductivity to the electrodes, and any conductive material can be used as long as it does not cause a chemical change in the battery that is constructed.Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0065] The current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0066] <Electrolyte> The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0067] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0068] The non-aqueous organic solvent may be a carbonate, ester, ether, ketone, alcohol, or aprotic solvent, or a combination thereof.

[0069] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Also, cyclohexanone can be used as the ketone solvent. Ethyl alcohol, isopropyl alcohol, etc. can be used as the alcohol solvent, and nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which can contain a double bond, an aromatic ring, or an ether group), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane and 1,4-dioxolane, sulfolanes, etc. can be used as the aprotic solvent.

[0070] The non-aqueous organic solvents can be used alone or in combination of two or more kinds.

[0071] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.

[0072] The lithium salt is a substance that dissolves in an organic solvent, acts as a source of lithium ions in a battery, enables the basic operation of a lithium secondary battery, and plays a role in promoting the movement of lithium ions between the positive electrode and the negative electrode. A representative example of a lithium salt is LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiClO 4 , LiAlO 2 , LiAlCl 4 , LiPO 2 F 2 , LiCl, LiI, LiN(SO 3 C 2 F 5 ) 2 , Li(FSO 2 ) 2 N(Lithium bis(fluorosulfonyl)imide (LiFSI), LiC 4 F 9 SO 3 , LiN(C x F2 x+1 SO 2 )(C y F 2y+1 SO 2 ) (wherein x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0073] [Separator] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.

[0074] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0075] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyether sulfone, polyphenylene oxide, cycloolefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0076] The organic material may include a polyvinylidene fluoride polymer or a (meth)acrylic polymer.

[0077] The inorganic material is Al 2 O 3 , SiO 2 , TiO 2 , SnO 2 , CEO 2 , MgO, NiO, CaO, GaO, ZnO, ZrO 2 , Y 2 O 3 , SrTiO 3 , BaTiO3 , Mg(OH) 2 The inorganic particles may include, but are not limited to, inorganic particles selected from silica, boehmite, and combinations thereof.

[0078] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0079] Lithium secondary batteries can be classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, into cylindrical, square, coin, pouch, etc. depending on the shape, and into bulk type and thin film type depending on the size. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted.

[0080] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular battery, FIG. 2 shows a square battery, and FIGS. 3 and 4 show a pouch battery. Referring to FIGS. 1 to 4, the lithium secondary battery 100 can include an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 can be impregnated with an electrolyte (not shown). The lithium secondary battery 100 can include a sealing member 60 that seals the case 50 as shown in FIG. 1. In addition, in FIG. 2, the lithium secondary battery 100 can include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.

[0081] The lithium secondary battery according to an embodiment of the present invention may be applied to automobiles, mobile phones, and / or various types of electric devices, but the present invention is not limited thereto.

[0082] Examples and comparative examples of the present invention are described below. The following examples are merely one embodiment of the present invention, and the present invention is not limited to the following examples.

[0083] Example 1 Large-grain LiFePO with an average particle size (D50) of 5 μm 4 Small LiFePO particles with an average particle size (D50) of 0.5 μm 4 The particles were mixed in a weight ratio of 6:4 to prepare a positive electrode active material.

[0084] 90% by weight of the positive electrode active material, 5% by weight of polytetrafluoroethylene binder, and 5% by weight of Ketjen Black conductive material were dry mixed at a speed of 5000 rpm for 10 minutes, and the mixture was pressed out to prepare a sheet-type free-standing film positive electrode active material layer.

[0085] The positive electrode active material layer was laminated on an aluminum foil current collector to prepare a positive electrode. The loading level of the positive electrode active material layer in the prepared positive electrode was 40 mg / cm. 2 and the polytetrafluoroethylene binder was fibrillated polytetrafluoroethylene.

[0086] A negative electrode active material layer slurry was prepared by mixing 98% by weight of natural graphite negative electrode active material, 1% by weight of styrene butadiene rubber, and 1% by weight of carboxymethyl cellulose in an aqueous solvent. The negative electrode active material layer slurry was applied to a copper foil current collector, dried, and rolled to prepare a negative electrode.

[0087] A full cell having a volume of 0.96 L was manufactured using the positive electrode, the negative electrode, and an electrolyte. The electrolyte was 1M LiPF 6A mixed solvent (volume ratio 2:1:7) of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate in which fluoroethylene carbonate was added in an amount of 3.5% by weight based on the total weight of the mixed solvent was used.

[0088] Example 2 Large-grain LiFePO with an average particle size (D50) of 5 μm 4 Small LiFePO particles with an average particle size (D50) of 0.5 μm 4 A positive electrode and a full cell having a volume of 0.96 L were manufactured in the same manner as in Example 1, except that the particles were mixed in a weight ratio of 65:35. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 60 mg / cm. 2 and the polytetrafluoroethylene binder was fibrillated polytetrafluoroethylene.

[0089] Example 3 Large-grain LiFePO with an average particle size (D50) of 10 μm 4 Small LiFePO particles with an average particle size (D50) of 1.0 μm 4 A positive electrode and a lithium secondary battery having a volume of 0.96 L were manufactured in the same manner as in Example 1, except that the particles were used. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 70 mg / cm. 2 and the polytetrafluoroethylene binder was fibrillated polytetrafluoroethylene.

[0090] Example 4 Large-grain LiFePO with an average particle size (D50) of 10 μm 4 Small LiFePO particles with an average particle size (D50) of 2.0 μm 4 A positive electrode and a lithium secondary battery having a volume of 0.96 L were manufactured in the same manner as in Example 1, except that the particles were used. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 80 mg / cm. 2 and the polytetrafluoroethylene binder was fibrillated polytetrafluoroethylene.

[0091] Comparative Example 1 Large-grain LiFePO with an average particle size (D50) of 5 μm 4 Small LiFePO particles with an average particle size (D50) of 0.5 μm 4 The particles were mixed in a weight ratio of 60:40 to prepare a positive electrode active material.

[0092] 98% by weight of the positive electrode active material, 1% by weight of polytetrafluoroethylene binder, and 1% by weight of Ketjen Black were mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material layer slurry.

[0093] The positive electrode active material layer slurry was applied to an aluminum foil current collector, dried, and rolled to prepare a positive electrode. In the prepared positive electrode, the loading level of the positive electrode active material layer was 30 mg / cm. 2 It was.

[0094] The same procedure as in Example 1 was carried out using the positive electrode to manufacture a lithium secondary battery having a volume of 0.96 L.

[0095] Comparative Example 2 Instead of polytetrafluoroethylene binder, polyvinylidene fluoride binder is used, and large-grain LiFePO with an average particle size (D50) of 20 μm is produced. 4 Small LiFePO particles with an average particle size (D50) of 2.5 μm 4 A positive electrode and a lithium secondary battery having a volume of 0.96 L were manufactured in the same manner as in Comparative Example 1, except that the particles were used. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 35 mg / cm. 2 It was.

[0096] Comparative Example 3 Large-grain LiFePO with an average particle size (D50) of 30 μm 4 A positive electrode and a lithium secondary battery having a volume of 0.96 L were manufactured in the same manner as in Example 1, except that only the particles were used as the positive electrode active material. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 38 mg / cm. 2 It was.

[0097] Comparative Example 4 Small grain LiFePO with an average grain size (D50) of 0.05 μm 4 A positive electrode and a lithium secondary battery having a volume of 0.96 L were manufactured in the same manner as in Example 1, except that the positive electrode active material was used. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 25 mg / cm. 2 It was.

[0098] Experimental Example 1) Current density (mAh / cm 2 )evaluation The current density of the positive electrodes produced in Examples 1 to 4 and Comparative Examples 1 to 5 was calculated according to the following formula 1. For example, when the current density of Example 1 was calculated according to formula 1, it was 40 (mg / cm 2 )*90(%)*140(mAh / g)=5(mAh / cm 2 ) was.

[0099] [Formula 1] Current density = loading level (mg / cm 2 )*Active material ratio (%)*LFP capacity (mAh / g)

[0100] In the above formula 1, the LFP capacity is LiFePO 4 The experimental capacity is 140mAh / g.

[0101] Experimental example 2) Energy density (Wh / L) evaluation The energy density for the half cells of Examples 1 to 4 and Comparative Examples 1 to 4 was calculated using the following formula 2. The results are shown in Table 1. For example, the energy density of Example 1 was calculated using the following formula 2 as 3.2 (V) * 135 (Ah) / 0.96 (L) = 450 (Wh / L).

[0102] [Formula 2] Energy density (Wh / L) = theoretical voltage (Nominal Voltage, V) * battery capacity (Ah) / battery volume (L)

[0103] In the above formula 2, the battery capacity is a value calculated from the current density value obtained in the above example 1.

[0104] [Table 1]

[0105] As shown in Table 1, the batteries of Examples 1 to 4 had a density of 40 mg / cm 2 It is possible to manufacture cathodes with loading levels of 5 mAh / cm 2 It is possible to manufacture a positive electrode having a high current density of 450 Wh / L or more. This makes it possible to obtain a positive electrode having a high energy density of 450 Wh / L or more, and as a result, a high-capacity battery of 135 Ah or more can be obtained.

[0106] On the other hand, the positive electrodes of Comparative Examples 1 and 2, which were produced by a wet process, had a capacitance of 30 mg / cm 2 and 35 mg / cm 2 Positive electrodes having low loading levels were fabricated, resulting in low current density, energy density and battery capacity.

[0107] At the same time, even if it is produced by dry method, large grain LiFePO 4 In the case of Comparative Example 3, where only particles were used, the loading level increased slightly, but was 38 mg / cm 2 However, a positive electrode having a loading level still lower than that of the Example was produced. As a result, the current density, energy density, and battery capacity were all lower than those of the Example. In addition, the small-grain LiFePO 4 In the case of Comparative Example 4, in which only particles were used, the density was 25 mg / cm 2 Various cathodes have been fabricated with very low loading levels of 0.1% and therefore with significantly lower current densities, energy densities and battery capacities.

[0108] The present invention is not limited to the above-mentioned embodiments, and can be manufactured in various different forms, and a person skilled in the art to which the present invention belongs can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential features of the present invention. Therefore, the above-described embodiments should be understood to be illustrative in all respects and not limiting.

Claims

1. A positive electrode for a lithium secondary battery comprising a dry positive electrode active material layer comprising a positive electrode active material of large-grain lithium iron phosphate particles and small-grain lithium iron phosphate particles, and a polytetrafluoroethylene binder.

2. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein a mixing ratio of the large lithium iron phosphate particles to the small lithium iron phosphate particles is 99:1 to 60:40 by weight.

3. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the large lithium iron phosphate particles are larger in size than the small lithium iron phosphate particles.

4. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein a ratio of the size of the large lithium iron phosphate particles to the size of the small lithium iron phosphate particles is 1.5:1 to 19:

1.

5. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the large lithium iron phosphate particles have a size of 2.5 μm to 20 μm.

6. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the small lithium iron phosphate particles have a size of 0.1 μm to 2.5 μm.

7. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the polytetrafluoroethylene is fibrillated polytetrafluoroethylene.

8. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the large lithium iron phosphate particles and the small lithium iron phosphate particles are the same or different and are represented by the following Chemical Formula 1: [Chemical formula 1] Li a Fe 1-x M x PO 4 (In the above formula 1, 0.90≦a≦1.8, 0≦x≦0.7, and M is Mg, Co, Ni, Mn, or a combination thereof.)

9. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the content of the polytetrafluoroethylene binder is 0.1% by weight to 5.0% by weight based on 100% by weight of the dry positive electrode active material layer.

10. The positive electrode for a lithium secondary battery according to claim 1 , wherein the dry positive electrode active material layer further comprises a conductive material.

11. 2. The positive electrode for a lithium secondary battery according to claim 1, wherein the energy density of the positive electrode is 400 Wh / L to 490 Wh / L.

12. The loading level of the dry positive electrode active material layer is 40 mg / cm 2 ~90mg / cm 2 The positive electrode for a lithium secondary battery according to claim 1 ,

13. The positive electrode has a capacity of 5 mAh / cm 2 2. The positive electrode for a lithium secondary battery according to claim 1, which has a current density of at least 1000 nm.

14. The positive electrode has a capacity of 5 mAh / cm 2 ~8mAh / cm 2 2. The positive electrode for a lithium secondary battery according to claim 1, having a current density of

15. The positive electrode according to any one of claims 1 to 14; A negative electrode; and A lithium secondary battery comprising a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Thin film pole piece and preparation method and application thereof

    CN115881893A

  • Recycling and reusing method of positive electrode material and regenerated membrane of positive electrode material

    CN116259706A

  • Lithium iron phosphate positive electrode material with nano-microporous structure and preparation method of lithium iron phosphate positive electrode material

    CN116692819A

  • Cathode unit and method for manufacturing the cathode unit

    JP2022514855A

  • Lithium iron phosphate positive electrode sheet and manufacturing method thereof, lithium iron phosphate lithium-ion battery

    JP2023519287A